Indoor Surveillance Security Robot with a Self-Propelled Patrolling Vehicle - Hou-Tsan Lee; Wei-Chuan Lin; Ching-Hsiang Huang (Journal of Robotics)
Self-propelled patrolling vehicles can patrol periodically in the designed area to ensure the safety like men do. The proposed vehicle cannot only save manpower, but also ensure the performance without mistakes caused by man. It is different from the traditional patrolling system which is limited by the manpower and the fixed camera positions. To improve such situation, this paper proposes a self-propelled patrolling vehicle which can move automatically to a wider range and record the monitored image by IPCAM within a predefined patrolling route. Besides, the user can use the mobile device or website to connect to the vehicle at anytime and anywhere and control it to move to the position to get the indoor image user wants. The position of self-propelled vehicles can be detected by the RFID reader as a feedback and be shown on the PC screen and smart phone. The recorded images can be also transmitted back to the server via WiFi system for face tracking and discriminating analysis. On the other hand, the self-propelled vehicle patrolling routes can be modified by the Android smart-phone remote-control module. When some defined events occur, the build-in MSN module will notice users by sending messages to PC and smart phone. Experimental results are given in the paper to validate its performance.